Heterogeneous landscape formation and urban experiences in the Floresta neighborhood, Porto Alegre/state of Rio Grande do Sul - Apollo, Luiz Henrique; Gonzatti de Souza, Vitoria (Pontifícia Universidade Católica de São Paulo, 2021)
The article presents the complex relationships between social processes and material spaces in the Floresta neighborhood, included in the history of socioeconomic changes that occurred in the 4th District of Porto Alegre. They have been materialized by different elements, since the process of their industrialization, emptying and reappropriation. Thus, urban environments are built according to the uses organized by social actors in territorialities, belonging to the three urban borders that constitute this space of contrasts. The qualitative methodology of explanatory research was applied, including techniques such as walking and the use of photographic and written records. With this approach, typifications of physical spaces and their uses were identified, expressing, in a segmented way, experiences and encounters in different combinations of bonds, memories and conflicts.